A C-Arm-Free Minimally Invasive Technique for Spinal Surgery: Cervical and Thoracic Spine - Masato Tanaka; Konstantinos Zygogiannnis; Naveen Sake; Shinya Arataki; Yoshihiro Fujiwara; Takuya Taoka; Thiago Henrique de Moraes Modesto; Ioannis Chatzikomninos (Medicina, 2023)
Background and Objectives: C-arm-free MIS techniques can offer significantly reduced rates of postoperative complications such as inadequate decompression, blood loss, and instrumentation misplacement. Another advantageous long-term aspect is the notably diminished exposure to radiation, which is known to cause malignant changes. This study emphasizes that, in some cases of spinal conditions that require a procedural intervention, C-arm-free MIS techniques hold stronger indications than open surgeries guided by image intensifiers. Materials and Methods: This study includes a retrospective analysis and review of various cervical and thoracic spinal procedures, performed in our hospital, applying C-arm-free techniques. The course of this study explains the basic steps of the procedures and demonstrates postoperative and intraoperative results. For anterior cervical surgery, we performed OPLL resection, while for posterior cervical surgery, we performed posterior fossa decompression for Chiari malformation, minimally invasive cervical pedicle screw fixation (MICEPS), and modified Goel technique with C1 lateral mass screw for atlantoaxial subluxation. Regarding the thoracic spine, we performed anterior correction for Lenke type 5 scoliosis and transdiscal screw fixation for diffuse idiopathic skeletal hyperostosis fractures. Results: C-arm-free techniques are safe procedures that provide precise and high-quality postoperative results by offering sufficient spine alignment and adequate decompression depending on the case. Navigation can offer significant assistance in the absence of normal anatomical landmarks, yet the surgeon should always appraise the quality of the information received from the software. Conclusions: Navigated C-arm-free techniques are safe and precise procedures implemented in the treatment of surgically demanding conditions. They can significantly increase accuracy while decreasing operative time. They represent the advancement in the field of spine surgery and are hailed as the future of the same.